ANALISIS TREN PERKIRAAN STATISTIK KEMATIAN INDIKATOR GDR DAN NDR DI RUMAH SAKIT PKU MUHAMMADIYAH TEMANGGUNG PERIODE 2021-2025 - Via Amarsya; Yuli Fitriyah; Regita Urbanantika (Journal of Hospital Administration and Management (JHAM), 2026)
Mortality statistics, including the Gross Death Rate and Net Death Rate, are crucial parameters for assessing the quality of hospital services. PKU Muhammadiyah Temanggung Hospital experienced significant fluctuations in mortality rates, requiring in-depth analysis post-pandemic. This study aims to analyze past trends and predict GDR and NDR values for the 2026-2030 period as a benchmark for strategic management decision-making. The research method employed a mixed-method approach with a sequential explanatory design. Quantitative analysis (2021–2025) used the least squares method, while qualitative aspects were explored through structural interviews to identify managerial and clinical factors that influence mortality rates. The results showed a GDR, which peaked at 42.83‰ in 2021, decreasing to 24.56‰ in 2025. The NDR decreased from 25.57‰ to 11.36‰. Epidemiologically, there has been a shift in the leading cause of death from COVID-19 in 2021 to stroke in 2022-2025. Prediction results estimate a GDR of (-1.18‰) and an NDR of (-7.19‰) in 2030. This decline is driven by improved facilities, updates to the emergency department, specialist doctors, and strengthening intensive care (ICU/HCU) services. The study's conclusions indicate that quality has consistently improved in line with mortality trends that are below the Indonesian Ministry of Health standards. Recommendations for hospitals include optimizing 24-hour stroke unit services, integrating statistical visualization into information systems, and strengthening official documentation of death audits with medical committees to support accreditation.